MORALITY AS A CRITERION FOR A CLAUSE OF GOOD PRACTICES IN THE LIGHT OF SELECTED ACTS OF POLISH COMMERCIAL LAW - Bider, Marcin; Interlandi, Roberto (Management and Administration Journal, 2020)
This article employing historical-legal methods presents the relationship between an extra-legal axiology and the norms of commercial law. The standard of morality is presented among several criteria of the good practices clause. Axiological pluralism demands that the criterion of morality be recognized in the light of constitutional values. Freedom of economic trade is a basic value that can only be restricted by law. At the same time, legal norms require justification through the system of moral norms. Non-legal norms incorporated into the system of commercial law make trade more flexible and allow a judge to resolve conflicts in economic trade.